Trend of HIV seroprevalence among antenatal women at tertiary care hospital in North India, eleven years retrospective study - Dwivedi, Seema; Jahan, Uruj; Srivastava, Roli; Agnihotri, Anshu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Human Immunodeficiency virus (HIV)/Acquired immunodeficiency syndrome (AIDS) is spreading worldwide at an alarming rate and India has third largest number of estimated people living with HIV/AIDS in the world. Estimating the HIV seroprevalence in a low risk population such as pregnant women provide essential information for monitoring trend of HIV in general population and assist in prevention from mother to child transmission (PMTCT) of HIV infection. Only few studies are available from this part of northern India. So we carried out this study to find out seroprevalence of HIV in pregnant women at tertiary care hospital of Uttar Pradesh, India. Methods: Blood samples were collected from pregnant women attending antenatal clinic of GSVM Medical college, Kanpur, U.P, India. after pretest counseling and inform consent from September 2005 to July 2016. The samples are tested as per National AIDS Control Organization (NACO) guidelines. Results: Among 38794 pregnant women counseled, 34924(90.02%) accepted HIV testing. 102 women out of 34924 were found HIV seropositive with prevalence rate of 0.3%. Among seropositive women, majority were Hindu (88.2%), housewife (89.2%), multigravida (62.7%), studied up to primary or secondary (78.4%), of low socio-economic status (74.5%) and belongs to rural area (67.6%). Majority of HIV seropositive (34.3%) women were in age group of 25-30 years followed by 21-25years (25.4%). HIV seroprevalence rates showed an increasing trend from 0.14% in 2006 to 0.49% in 2016 (till July). Conclusions: Seroprevalence of HIV infection amongst antenatal women was 0.3%in past 11 years which is in increasing trend in contrast to other studies and slightly higher than national projection (0.29%). It concludes that it is right time to strengthen prevention of mother to child transmission (PMTCT) services by joint efforts of the private and public sectors.